Customer loyalty in the Platanitos store, La Victoria - 2022 - Seminario Unzueta, Randall Jesús (2022)
Objective: to determine customer loyalty in the Platanitos store - La Victoria, 2022. Materials and Methods: quantitative research, applied type, non-experimental, correlational, cross-sectional design, descriptive level, with a population of 204 customers who visit the Platanitos store. The data collection technique is the survey, the instrument is the questionnaire, made up of 18 ítems for the loyalty variable grouped into 3 dimensions and 3 indicators in each dimension. Results: Of the total number of respondents from the Platanitos store, it can be seen that 47.5% indicate that loyalty is at a very high level; given that 30% indicate that loyalty is high, 16% say that loyalty is fair; on the other hand, 4.4% say that loyalty is at a low level and 0.5% say that it is at a very low level. Conclusions: it is concluded that the products offered have a regular level of acceptance, customers consider that a good quality of service is provided, they have a regular experience and considering that the communication of the brand with its customers is regular; therefore, it should be improved.